Ultrahigh Dielectric Permittivity of a Micron-Sized Hf0.5Zr0.5O2 Thin-Film Capacitor After Missing of a Mixed Tetragonal Phase - Wen Di Zhang; Bing Li; Wei Wei Wang; Xing Ya Wang; Yan Cheng; An Quan Jiang (Nano-Micro Letters)
Highlights Ferroelectric-to-nonferroelectric transition occurs in a micron-sized Hf0.5Zr0.5O2 thin-film capacitor with the generation of a giant dielectric permittivity. Synchrotron X-ray micro-diffraction patterns show missing of a mixed tetragonal phase in the capacitor. The stored charge density of the capacitor is as high as 183 μC cm-2 at an operating voltage/time of 1.2 V/50 ns at cycle numbers of more than 1012 without inducing dielectric breakdown.